2022
DOI: 10.14573/altex.2202131
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in vitro experimental variation in kinetic parameters on physiologically based kinetic (PBK) model simulations

Abstract: In vitro toxicokinetic data are critical in meeting an increased regulatory need to improve chemical safety evaluations towards a better understanding of internal human chemical exposure and toxicity. In vitro intrinsic hepatic clearance (CLint), the fraction unbound in plasma (Fup), and the intestinal apparent permeability (Papp) are important parameters as input in a physiologically based kinetic (PBK) model to make first estimates of internal exposure after oral dosing. In the present study we explored the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…26 ■ METABOLISM AND TOXICOKINETIC MODELING Generic PBPK models can be used to predict basic kinetics properties of the A.S. 27 These assays can be off-the shelf commercial models or the basic HTTK model, like those outlined in the USEPA presentation "Rapid PBPK modeling with the HTTK model". 28 These can also be occasionally parametrized with high throughput screenings for certain kinetic parameters, such as Caco-2 cell screening for oral absorption, 29 liver microsomal clearance for metabolism kinetics, 30 and plasma protein binding 31 for distribution kinetics. Further evaluation of metabolic stability and pathways is key to predicting the fate of a pesticide in the environment, which is critical to the assessment of the potential exposure and risks to humans and ecological systems.…”
Section: ■ In Silico Assessmentsmentioning
confidence: 99%
“…26 ■ METABOLISM AND TOXICOKINETIC MODELING Generic PBPK models can be used to predict basic kinetics properties of the A.S. 27 These assays can be off-the shelf commercial models or the basic HTTK model, like those outlined in the USEPA presentation "Rapid PBPK modeling with the HTTK model". 28 These can also be occasionally parametrized with high throughput screenings for certain kinetic parameters, such as Caco-2 cell screening for oral absorption, 29 liver microsomal clearance for metabolism kinetics, 30 and plasma protein binding 31 for distribution kinetics. Further evaluation of metabolic stability and pathways is key to predicting the fate of a pesticide in the environment, which is critical to the assessment of the potential exposure and risks to humans and ecological systems.…”
Section: ■ In Silico Assessmentsmentioning
confidence: 99%
“…It must be noted that the testing approach described in the scientific opinion (EFSA PPR Panel et al, 2021b) was not developed to obtain chemical-specific input parameters for PBK models. It is therefore recommended to develop a harmonised guidance to highlight the requirements for generating reliable chemical-specific input parameters for PBK models and illustrate their use through relevant case studies so that these can be used for regulatory applications as demonstrated recently in the OECD guidance and related case studies (OECD, 2021a, b;Paini et al, 2019;Punt et al, 2023).…”
Section: Integration Of In Vitro Kinetic Data In Physiologically-base...mentioning
confidence: 99%